PENGARUH INTENSITAS KONSUMSI CONTENT DIGITAL TRIVIAL PLATFORM TIKTOK TERHADAP PERKEMBANGAN KOGNITIF SISWA KELAS VIII SMP NEGERI 2 MASARAN TAHUN PELAJARAN 2025/2026 - Rujito, Bambang; Ersta Kusumaningtyas, Lydia; Dwi Sholikhah, Linda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examined the effect of trivial digital content consumption intensity on the TikTok platform on the cognitive development of eighth-grade students at SMP Negeri 2 Masaran in the 2025/2026 academic year. Using a quantitative ex post facto design, data were collected from 159 respondents selected via cluster sampling from a population of 254 students across five classes. A self-developed questionnaire, validated for reliability (Cronbach's Alpha of 0.870 for consumption intensity and 0.909 for cognitive development), measured cognitive development across three aspects: attention, memory, and executive function. Simple linear regression, conducted after classical assumption testing, revealed a significant negative effect of consumption intensity on cognitive development (F = 54.190, p = 0.000), with the independent variable explaining 25.8% of the variance (R² = 0.258) and a regression coefficient of -0.677, indicating that higher consumption intensity corresponds to lower cognitive development. This negative effect was also significant for each cognitive aspect individually: attention (R² = 0.211), memory (R² = 0.198), and executive function (R² = 0.227). These findings underscore the need for improved digital literacy and active parental and teacher guidance in students' social media use. Keywords: trivial digital content, TikTok, cognitive development, consumption intensity, junior high school students